Teacher's Perception, Character Formation of Grade Students: Case Study at Primary School in City of Palangka Raya - Dian Sisianti; Septiani; Yeri Iriani; Kornes Senik (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this research is to find out the teacher's perception of character development in normal students and children with special needs in an elementary school in Palangka Raya. The role of the teacher in this school is important for the creation of the character or personality of the students. This research method is a qualitative method by finding sources through interviews, then factualizing it, then creating themes that are close to the author's research. The results of the study show that teachers work hard and take their time to achieve these tasks both inside and outside of school in terms of intelligence, morals and character.